Responsiveness of hand-held dynamometry for measuring changes in trunk muscle strength in people with chronic low back pain - Shouq Althobaiti; Janet A. Deane; Deborah Falla (BMC Musculoskeletal Disorders)
Abstract Objective To assess the responsiveness of a hand-held dynamometer (HHD) in evaluating changes in trunk isometric strength in people with chronic low back pain (LBP). Background Reduced trunk muscle strength has been associated with pain incidence and severity in people with chronic LBP. Trunk muscle strength is an important functional outcome that is measured in clinical practice and research. However, the responsiveness of clinical tools such as HHD for measuring changes in trunk muscle strength remains underexplored. Methods Maximum isometric trunk strength was measured using both a HHD and an isokinetic dynamometer (ID) in 21 participants with chronic LBP both before and after 6 weeks of progressive trunk resistance exercises. Effect sizes (ES) and standardised response mean (SRM) were used to evaluate the internal responsiveness of the HHD measures. External responsiveness was determined by correlating the change scores measured with the HHD with those obtained using the ID. Results Following the progressive resistance exercise programme, there was a significant improvement in trunk muscle strength measured with the HHD with moderate to large ES (0.40–0.85) and SRM (0.60- 0.74), indicating moderate to high internal responsiveness. Pearson's correlations revealed a weak correlation between changes in trunk strength measured with the HHD and those measured with the ID (r = 0.22- 0.26), indicating inadequate external responsiveness. Conclusions Although the use of a HHD was shown to have internal responsiveness for detecting changes in trunk muscle strength, the inadequate external responsiveness warrants further investigation. Future research should also explore the responsiveness of HHD in people with chronic LBP with higher pain and disability levels using comparable measurement setups.